Airway hyperresponsiveness in elite swimmers: Is it a transient phenomenon? - Bougault, V.; Turmel, J.; Boulet, L. P. (Journal of Allergy and Clinical Immunology, 2011)
Airway hyperresponsiveness is highly prevalent in competitive swimmers, but it is unknown whether this is transient or persistent. Objectives